An analysis of Socio-Demographic Profile of Asphyxial Deaths in Western Mumbai Region - Sachin s. Sonawane1 , Rajesh B. Sukhdeve2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: the study is conducted to determine epidemiology of violent asphyxia deaths in the western Mumbai region and variation in types of asphyxia deaths in relation to age and gender. Methods: Study was conducted in department of forensic medicine of H. B. T. Medical College & cooper Hospital, Mumbai for period (2 years) of January 2015 to December 2016. Total 3114 of autopsies were conducted during the period of which 187(6%) were asphyxial death which are included in this study. Result: 187 out of 3114 medicolegal autopsies were of asphyxial death making incidence rate 5.87% of asphyxial death. Age group most commonly involved in asphyxial death was 21-30 years constitutes 28.8% cases. Male victims constitute of 60.42% cases and female victims were 39.58% cases. Drowning is common in age group 1-20 years constitutes 94.4% of all drowning deaths. Age group 1-10 years all the asphyxial deaths were due to drowning. Hanging is commonest in age group 21-30 years and it constitutes 41.22% of hanging case. Conclusion: Males and young age group population between 11–40 years are more susceptible victims of violent asphyxial deaths. Hanging and drowning was most common cause in this age group. Both types of asphyxial deaths in young population are preventable and needs to be rectified.